2015
DOI: 10.1007/s10995-015-1903-y
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Life Planning: A Cross-Sectional Study of What College Students Know and Believe

Abstract: Objectives The Centers for Disease Control and Prevention recommends a reproductive life plan (RLP) to promote individual responsibility for preconception health. The objectives of this study were to determine existing awareness of RLPs in a cohort of reproductive-age adults and to evaluate their knowledge level and beliefs about reproductive life planning. Methods We performed a cross-sectional survey study of adults ages 18-40 years old seeking care at the student health center of a large public university. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Fertility knowledge has been shown to have a significant influence on family planning for women [11] and lack of fertility knowledge has been found to impede preconception care for men [12]. Furthermore, young adults' fertility knowledge has been reported to be low in general [13], making it necessary to assess fertility knowledge among Korean college students and to determine whether it affects self-efficacy toward pregnancy planning. Pregnancy planning has also been found to be associated with maternal characteristics such as age, income, smoking, alcohol drinking, stress, and depression [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Fertility knowledge has been shown to have a significant influence on family planning for women [11] and lack of fertility knowledge has been found to impede preconception care for men [12]. Furthermore, young adults' fertility knowledge has been reported to be low in general [13], making it necessary to assess fertility knowledge among Korean college students and to determine whether it affects self-efficacy toward pregnancy planning. Pregnancy planning has also been found to be associated with maternal characteristics such as age, income, smoking, alcohol drinking, stress, and depression [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of communication and specific elements of RLP, women have reported that they value the straightforward and organized formatting of RLP interventions, opportunities for self-reflection, 38 and being prompted to ask questions and discuss specific topics of interest with their health providers. 38 39 Callegari et al 40 and Kransdorf et al 41 found that women desired provider-initiated and nonjudgmental counseling that incorporated their preferences, desires, and values.…”
Section: Discussionmentioning
confidence: 99%
“…Unawareness could be related to individual factors such as low health literacy, but could also be affected by factors at provider level. Kransdorf et al for example reported that young women in college did not discuss reproductive life planning or preconception health with their providers, despite expressing interest in doing so [ 29 ]. A qualitative study in Italy found a lack of awareness of preconception health and care, not only among women of childbearing age, but also among midwives, medical doctors and nurses [ 30 ].…”
Section: Discussionmentioning
confidence: 99%